2014
DOI: 10.2174/2211550103666140508203241
|View full text |Cite
|
Sign up to set email alerts
|

Production of β-Glucosidase by Aspergillus niger on Wheat Bran and Glycerol in Submerged Culture: Factorial Experimental Design and Process Optimization

Abstract: The goal of this study was to develop a fermentation process for the production of β-glucosidase, an important enzyme in the hydrolysis of lignocellulose and has many applications in food and flavor industries, using low-cost agricultural residues as substrates. Based on statistical experimental design, high-titer production of β-glucosidase on wheat bran and glycerol by Aspergillus niger in a submerged culture was achieved. A 2-level Plackett-Burman design was first used to screen the bioprocess parameters af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…The studies reported that the activities of b-glucosidase produced by both these fungi peaked when the pH of the broth cultures was maintained at pH 5. In fact, the preferred neutral optimal pH in the broth cultures of T. harzianum is similar to that reported for an A. niger isolate [51].…”
Section: Effect Of Temperature and Phsupporting
confidence: 81%
“…The studies reported that the activities of b-glucosidase produced by both these fungi peaked when the pH of the broth cultures was maintained at pH 5. In fact, the preferred neutral optimal pH in the broth cultures of T. harzianum is similar to that reported for an A. niger isolate [51].…”
Section: Effect Of Temperature and Phsupporting
confidence: 81%
“…Fontana et al [42] observed a minimum pH of 2.7 in a STB, reaching 5.10 at the end of the fermentation process by Aspergillus oryzae. This drop in pH Abdella et al [55] Peniciliium echinulatum S1M29 Cellulose plus glycerol Schneider et al [56] BGL beta-glucosidase activity, BXL beta-xylosidase activity, LHW-pretreated CC corncob pretreated by liquid hot water, OPEFB oil palm empty fruit bunch, DSB sugarcane bagasse pretreated by steam followed by delignification with NaOH, MC microcrystalline cellulose, n.d. not determined a Medium also containing sucrose, soybean meal, wheat bran in lower concentrations The values presented correspond to mean values of two replicate experiment could be related to the production of acid metabolic by-products, as well as with the acetic acid released from hemicellulose during the degradation of the lignocellulosic substrate by the produced xylanases. Similar trend in pH decrease was also reported by Khanahmadi et al [47] and Abdella et al [48].…”
Section: Influence Of Aeration and Agitation Rates In The Enzymatic Pmentioning
confidence: 99%
“…As a result, exquisite processes have been developed to culture A. niger strains in an effort to yield natural food‐grade enzymes (Aguilar, Augur, Favela‐Torres, & Viniegra‐González, ). Researchers have shown that A. niger can grow on some agricultural byproducts such as potato, jamun leaves, tea wastes (TW), and wheat bran (WB), and synthesize multiple enzymes via fermentation (Abdella, Elsayed Mazeed, Yang, & Elbaz, ; Ni, Chen, et al, ; Wang, Ni, Cai, & Xiao, ). Recently, the crude enzymes prepared from A. niger via fermentation on TW medium and wheat bran and orange peel (WBOP) medium have been found in our preliminary tests to be able to change and improve the aroma profile of instant Oolong tea.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, exquisite processes have been developed to culture A. niger strains in an effort to yield natural food-grade enzymes (Aguilar, Augur, Favela-Torres, & Viniegra-Gonz alez, 2001). Researchers have shown that A. niger can grow on some agricultural byproducts such as potato, jamun leaves, tea wastes (TW), and wheat bran (WB), and synthesize multiple enzymes via fermentation (Abdella, Elsayed Mazeed, Yang, & Elbaz, 2014;Wang, Ni, Cai, & Xiao, 2012).…”
mentioning
confidence: 99%